Perbandingan Profitabilitas Bank Konvensional Sebelum dan Setelah Hadirnya Fintech P2P Lending Periode 2014 – 2023 - Nurazizah, Putri Amalia; Noer Ridha, Noorsyah Adi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
This study aims to review whether there is a significant difference in the profitability of the conventional banking sector before and after the presence of start-up Fintech P2P Lending as measured by the level of profitability ratios ROA, NIM, and BOPO. Descriptive studies and quantitative methods are used in this study, with the population used, namely Conventional Banks listed on the Indonesia Stock Exchange during the period 2014 - 2023 with a total of 9 banks through purposive sampling method. The data used for processing is secondary data from the company's financial statements taken per year. Data processing was carried out using the SPSS 26 program by conducting Normality Test and Differential Test, which was carried out by the Paired Sample T-Test and Wilcoxon Signed Rank Test. The results showed that the ROA and NIM variables had a significant dissimilarity and effect before and after the presence of P2P lending, while for the BOPO variable there was no significant dissimilarity.